PENGARUH PEMBELAJARAN DIFERENSIASI BERBASIS STEAM TERHADAP HASIL BELAJAR IPAS SISWA SD AL-ISLAM PENGKOL - Mutiara, Devani; Attalina, Syailin Nichla Choirin; Hamidaturrohmah, Hamidaturrohmah (Universitas Muria Kudus, 2024)
The aim of this research is to find out whether there is an effect of implementing STEAM-based differentiation learning on science learning outcomes. The research method used in this research is a pre-experimental quantitative method with a One Group Pretest-Posttest design. The population of this study were fourth grade students at Elementary School Al-Islam Pengkol. The sample for this study was 26 students using a saturated sampling technique. Data was collected through a multiple choice written test. The pretest and posttest instrument questions were tested for validity and reliability. The data analysis technique used is the paired sample t test. The research results showed that there was a difference in the average science learning outcomes between the pretest and posttest. There was an increase in the average score between the pretest and posttest in student learning outcomes, namely from a score of 65 at the pretest to a score of 89 at the time of the posttest. This shows the influence of implementing a differentiation learning strategy with a STEAM approach on science and science learning outcomes at A Elementary School.l-Islam Pengkol.